UJI DAYA HAMBAT EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten) Steenis) TERHADAP PERTUMBUHAN BAKTERI Proteus vulgaris: INHIBITORY ACTIVITY OF BINAHONG LEAF EXTRACT (Anredera cordifolia (Ten) Steenis) ON THE GROWTH OF Proteus vulgaris BACTERIA - Khusniyah, Nisfatul; Ekawati, Evy Ratnasari; Sundari, Titik (Jurnal SainHealth, 2025)
Herbal plants in Indonesia have been widely used as traditional medicine. One natural resources is binahong leaves (Anredera cordifolia (Ten) Steenis). Microorganisms, namely bacteria, usually cause infectious diseases. Proteus vulgaris, is a common species of Proteus that is associated with infections in humans. This research aims to find out whether Binahong (Anredera Cordifilia (Ten) Steenis) leaf extract can inhibit the growth of Proteus vulgaris bacteria. The method used in this research is experimental. The subject of this research is Binahong (Anredera Cordifilia (Ten) Steenis) leaf extract dissolved in 96% ethanol. which was evaporated using a rotary vacuum evaporator. The inhibition test was carried out using well diffusion technique on Mueller Hinton Agar media Proteus vulgaris, the conclusion of this research is that concentrations of 20% 40% 60% 80% and 100% can be classified as moderate inhibitory activity.